An-aesthetic of disappearance. Section as project definer in the architecture of Albert Kahn - Pancorbo Crespo, Luis; Martín Robles, Inés (ZARCH. Journal of interdisciplinary studies in Architecture and Urbanism, 2014)
The vertiginous research developed in the Ford Company to continuously improve production processes while the Model T was the only model of the company, gave architect Albert Kahn, the rare possibility to redo several times the same industrial building. From the old Piquette Avenue to River Rouge complex, through the two Highland Park factories. Based on Gilbert Simondon’s theory of evolution of technical objects, we look for one of these evolutive cycles within the continuous rethinking of Albert Kahn in industrial architecture. In this developmental process of Kahn’s architecture towards the technical object, a reduction of project levels takes place. This reduction implies a disappearance of the plans and elevations. They don’t exist or pass to be a second level document that supports the section as the only major project document.